Students’ mathematical procedural fluency in solving mathematical problems in terms of mathematical resilience and gender - Muhammad Sazali; Nanang Priatna; Tatang Herman (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2026)
Mathematical resilience and gender are often associated with differences in students’ skills and ways of thinking while learning mathematics. This study aims to simultaneously describe students’ mathematical procedural abilities in terms of mathematical resilience and gender. Data were collected from 19 participants selected through purposive sampling based on criteria relevant to the research variables. A procedural fluency test and a student mathematical resilience questionnaire were used; both instruments had been previously validated by experts, who concluded that they were suitable for use. The data analysis technique employed was ANCOVA (Analysis of Covariance). The results indicated that both resilience and gender appeared to influence students’ mathematical procedural fluency; however, resilience was the factor that made a meaningful difference, not gender. Qualitative analysis, including resilience questionnaires, interviews, and test result descriptions, revealed that both male and female students can demonstrate strong mathematical procedural fluency when they possess high mathematical resilience. As a result, gender differences did not emerge as a significant influence, as both groups had equal opportunities when their mathematical resilience was high. The absence of a significant gender effect is suspected to be due to the relatively small sample size used in this study, which may not have provided sufficient statistical power to detect the actual effect. Due to the limitations of this study, these findings should be considered preliminary. Further research is needed using a larger sample size and more representative sampling to better examine the combined influence of gender and resilience on mathematical procedural fluency.